Delirium in Bipolar Disorder as a Triggering Factor to Cognitive Decline: A Case Report and Neuroprogression Insight - Ahadiah, Hayyunah Rohmatul; Syadza, Lailatus; Shafly, Moch Syafirul Nur; Asikah; Algristian, Hafid (Sinergi International Journal of Psychology, 2025)
Bipolar disorder is a major contributor to global disability, affecting not only mood regulation but also cognitive function, and its impact is often exacerbated by metabolic comorbidities such as type 2 diabetes mellitus, hypertension, and dyslipidemia. These comorbid conditions can lead to poorer clinical outcomes and increase the risk of neuropsychiatric complications such as delirium and cognitive impairment, which are frequently overlooked in clinical practice. This article aims to describe and analyze the case of a 31-year-old male with a history of bipolar disorder who presented with a hyperglycemic crisis and pneumonia, followed by the onset of acute delirium and subsequent cognitive decline. Through a descriptive clinical approach, the patient’s medical and psychiatric history, laboratory findings, and treatment course are reviewed to explore the complex interaction between mood disorders and metabolic dysfunction. The analysis reveals a strong link between metabolic dysregulation and worsening neuropsychiatric outcomes. This case underscores the importance of early detection and an integrated, multidisciplinary management approach to prevent long-term cognitive deterioration in patients with psychiatric disorders accompanied by metabolic conditions, offering important implications for future clinical practice.